Towards a structural understanding of the remodeling of the actin cytoskeleton. (June 2020) - Merino, Felipe; Pospich, Sabrina; Raunser, Stefan
Abstract: Actin filaments (F-actin) are a key component of eukaryotic cells. Whether serving as a scaffold for myosin or using their polymerization to push onto cellular components, their function is always related to force generation. To control and fine-tune force production, cells have a large array of actin-binding proteins (ABPs) dedicated to control every aspect of actin polymerization, filament localization, and their overall mechanical properties. Although great advances have been made in our biochemical understanding of the remodeling of the actin cytoskeleton, the structural basis of this process is still being deciphered. In this review, we summarize our current understanding of this process. We outline how ABPs control the nucleation and disassembly, and how these processes are affected by the nucleotide state of the filaments. In addition, we highlight recent advances in the understanding of actomyosin force generation, and describe recent advances brought forward by the developments of electron cryomicroscopy.